Faktor-faktor yang Berhubungan dengan Perilaku Penyalahgunaan Narkoba pada Remaja Usia 15-19 Tahun Di Kecamatan Semarang Utara Kota Semarang - Vikiat Ika Maharti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Drug abuse adolescent aged 15 – 19 years case is increasing every year, based on research BNN in Indonesia. Cases of drug abuse adolescent age 15-19 years on 2014 in Semarang city was 41.34%. Objective correspond for analyze factors related to the behavior of drug abuse adolescent age 15-19 years in the District of North Semarang. The method used quantitative with cross sectional approach. Population total of this research was 10.075 people with sample of 100 people. Result of this research were 53% of respondents at ever of drug abuse and 47% of respondents do not ever of drug abuse. The analysis data usesunivariateandbivariate with Chi-square statistical test(0.05 significance level). Respondents had good knowledge (53%), attitude which support behavior drug abuse (51%), easy access of drug(54%), strict regulation of drug (62%), peers attitude to support of drug abuse ( 67%), peers practice which support of drug abuse (61%), school support to not using drugs (81%), condition of family was not good (50%). The result of Chi-square test with p value < 0,05 showed that there are relations between affordability of drugs (p value 0,000), peer attitude ( p value 0,011) and peers practice (p value 0,000) with behavior adolescent drug abuse age 15-19 years in the north District of Semarang, Semarang City.